Tourism Development Through Indonesia – France Cooperation 2011-2016: Pembangunan Pariwisata Melalui Kerjasama Indonesia - Perancis Tahun 2011-2016 - Segarmas, Bambang; Yuniarti, Yuniarti; Wirawan, Rendy (Progress In Social Development, 2023)
As one of the most significant sectors in supporting the economy of a state, tourism sector is constantly advanced through cooperation with other states. The huge amount of economic distribution makes this sector essential in global economy. This must also affect Indonesia and France as two among many states which are quite popular as destination for overseas tourists. For Indonesia, French touristsis among the top of European travelers, though for France itself, Indonesian tourists only on placed on the fifth rank among Asians. Therefore, this circumstance drives both states to cooperate in advancing quantity and quality of tourism from Indonesia to France, vice versa. Furthermore, this research will elaborate tourism development through the cooperation between Indonesia and France in 2011-2016. This cooperation covers 6 areas which later rendered through three Joint Working Groups until 2016. The results shows that the cooperation increase the number of French tourist visit to Indonesia, and vice versa Indonesia to France. Nevertheless, in practice, there were still several points of cooperation that had previously been on the agenda in the JWG could not be implemented optimally. Sebagai salah satu sektor yang sangat penting dalam mendukung perekonomian suatu negara, sektor pariwisata terus dikembangkan melalui kerjasama dengan negara lain. Besarnya distribusi ekonomi menjadikan sektor ini penting dalam perekonomian global. Hal ini tentunya juga berimbas pada Indonesia dan Perancis sebagai dua di antara banyak negara yang cukup populer sebagai tujuan wisatawan mancanegara. Bagi Indonesia, wisatawan Prancis termasuk dalam top traveler Eropa, sedangkan untuk Prancis sendiri, wisatawan Indonesia hanya menempati peringkat kelima di antara orang Asia. Oleh karena itu, keadaan ini mendorong kedua negara untuk bekerja sama dalam memajukan kuantitas dan kualitas pariwisata dari Indonesia ke Prancis, begitu pula sebaliknya. Selanjutnya, penelitian ini akan mengelaborasi pengembangan pariwisata melalui kerjasama antara Indonesia dan Perancis pada tahun 2011-2016. Kerja sama ini mencakup 6 bidang yang kemudian disalurkan melalui tiga Joint Working Groups hingga tahun 2016. Hasil studi memperlihatkan bahwa kerjasama ini meningkatkan jumlah kunjungan wisatawan Perancis ke Indonesia, dan sebaliknya Indonesia ke Perancis. Meskipun demikian, dalam praktiknya, sampai dengan tahun 2016 masih ada beberapa butir kerjasama yang sebelumnya sudah diagendakan dalam JWG namun belum bisa terlaksana dengan maksimal.